Economic feasibility of SACC production for use in asphalt concrete (Research, Society and Development, 2021)
The Amazon region lacks surface raw material to obtain stone aggregates used in civil construction, more precisely in paving. Many studies have been conducted in order to identify an alternative material that can replace the use of rolled pebble and crushed stone in the production of asphalt concrete, due to the high cost of these raw materials as well as the worrying environmental impact arising from the extraction of rolled pebble from riverbeds. Among many alternative materials studied, the Sintered Aggregate of Calcined Clay (SACC) stands out as a replacement for these coarse aggregates, since there is a large reserve of clay in the State of Amazonas. The viability of this material has already been proven technically and environmentally. What is proposed in the study is the proof of the economic viability of SACC as a replacement for rolled pebble in the production of Hot Mix Asphalt (HMA) Concrete in the paving of highways in our region, especially in places far from Manaus.